Exchange Rate Fluctuations and Trade Flows : Evidence From the European Union - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper, 1998)
This paper analyzes the effects of exchange rate volatility on bilateral trade flows. Through use of a gravity model and panel data from western Europe, exchange rate uncertainty is found to have a negative effect on international trade. The results seem to be robust with respect to the particular measures representing exchange rate uncertainty. Particular attention is reserved for problems of simultaneous causality. The negative correlation between trade and bilateral volatility remains significant after controlling for the simultaneity bias. However, a Hausman test rejects the hypothesis of the absence of simultaneous causality.